Why Does Financial Strength Forecast Stock Returns? Evidence from Subsequent Demand by Institutional Investors - Choi, Nicole Y.; Sias, Richard W. (Review of Financial Studies, 2012)
[Using institutional investor demand as a proxy for revisions in sophisticated investors' expectations, we test whether financial strength information is gradually impounded over time. Consistent with the gradual incorporation of information, financial strength predicts both future returns and future institutional investor demand. Further consistent with the gradual incorporation of information, more sophisticated transient (high-turnover) institutions respond to financial strength signals prior to less sophisticated, nontransient institutions. A number of additional tests suggest that financial strength forecasts stock returns, at least in part, because it forecasts institutional demand, and institutional demand drives prices.]